H2 permeation and its influence on gases through a SAPO-34 zeolite membrane. (15th April 2023) - Zito, Pasquale Francesco; Brunetti, Adele; Caravella, Alessio; Barbieri, Giuseppe
Abstract: This work analysed the permeation of binary and ternary H2 -containing mixtures through a SAPO-34 membrane, aiming at investigating how hydrogen influences and its permeation is influenced by the presence of the other gaseous species, such as CO2 and CH4 . We considered the behaviour of various gas mixtures in terms of permeability and selectivity at various temperatures (25–300 °C), feed pressures (400–1000 kPa) and compositions by means of an already validated mass transport model, which is based on surface and gas translation diffusion. We found that the presence of CO2 and CH4 in the H2 -containing mixtures influences in a similar way the H2 permeation, reducing its permeability of about 80% compared to the single-gas value because of their stronger adsorption. On the other hand, H2 promotes the permeation of CO2 and CH4, causing an increment of their permeability with respect to those as single gases. These combined effects reflected in interesting selectivity values in binary mixture (e.g., CO2 /H2 about 11 at 25 °C, H2 /CH4 about 9 at 180 °C), which showed the potential of SAPO-34 membranes in treating of H2 -containing mixtures. Graphical abstract: Image 1 Highlights: Gas permeation of H2 -containing mixtures through a SAPO-34 membrane. Influence of temperature, feed pressure and composition on permeability and selectivity. Hindering effect of the strongly adsorbed CO2 and CH4 on H2 permeation. Promoting effect of the faster H2 on CO2 and CH4 permeation.